PEMBENTUKAN PERATURAN DESA (PERDES): TINJAUAN HUBUNGAN KEWENANGAN KEPALA DESA DAN BADAN PERMUSYAWARATAN DESA (BPD) - Elviandri; Indra Perdana (JOURNAL EQUITABLE, 2021)
This journal focuses on the problem of finding the relationship between the role of the Headman of Village and the Village Consultative Body (BPD) in drafting Village Regulations (Perdes). The journal research method used is the normative method. The results of the study carried out are the relationship between the authority of the Village Head and the Village Consultative Body (BPD). . As for the process of drafting and forming Aursati Village regulations in the preparation of village regulations carried out by the Village Consultative Body (BPD) with the Aursati Village Head, the drafting process uses the correct mechanism and all stages are passed well